Synthesis and optimization of photoluminescence properties in potential reddish orange emitting niobate phosphor for photonic device applications. (1st June 2021) - Jain, Rakshit; Sinha, Rachna; Sahu, Mukesh K.; Jayasimhadri, Mula
Abstract: A series of samarium ions (Sm 3+ ) activated barium sodium niobate (Ba2 NaNb5 O15 ) samples have been successfully synthesized via employing a solid‐state reaction technique. Single phase, crystalline tetragonal Ba2 NaNb5 O15 were formed and the crystallite size of the prepared sample varied with doping of Sm 3+ ions. The scanning electron microscopy (SEM) images of Ba2 NaNb5 O15 :Sm 3+ illustrate that the particles possess a non‐uniform spherical structure with some agglomeration. The prepared Ba2 NaNb5 O15 :Sm 3+ phosphors were efficiently excited with near‐ultraviolet (n‐UV) (406 nm) and emit strong visible emission peaks in the range 550–725 nm. The phenomenon of concentration quenching was detected after x  = 0.10 mol of Sm 3+ ions concentration for Ba2 NaNb5 O15, which arises due to non‐radiative energy transfer through dipole–dipole interaction among activator ions. Colour coordinates (0.586, 0.412) for the optimized phosphor lies in the visible reddish orange region. A bi‐exponential decay behaviour was observed for the photoluminescence decay curve of the optimized phosphor sample with an average decay time in milliseconds. The temperature dependent emission intensity confirms that the Ba2− x NaNb5 O15 : x Sm 3+ ( x  = 0.10 mol) phosphor exhibits adequate thermal stability having high value of activation energy (Δ E  = 0.201 eV). The comprehensive study and analysis of the as‐prepared samples suggest that the intense reddish orange emitting thermally stable Ba2 NaNb5 O15 :Sm 3+ phosphor can act as a potential luminescent material in phosphor coated lighting, solar cells and other photonic devices. Abstract : Samarium ions (Sm 3+ ) activated barium sodium niobate (Ba2 NaNb5 O15 ) phosphors were synthesized by a solid‐statereaction technique. The phosphor samples exhibit a reddish‐orangeemission with intense peak at 599 nm under an excitation wavelength of 406 nm. The emission intensity for the 4 G5/2 → 6 H7/2 transition was reduced to 67.70% at 150°Cand 58.85% at 200°C, which indicate that the prepared Ba2 NaNb5 O15 :Sm 3+ phosphor is thermally stable. The thermallystable Sm 3+ doped Ba2 NaNb5 O15 phosphor is a potential candidate for photonicdevice applications. Graphical image may be replaced with the image provided at attachemnts.